Cancer diaries: a study of communication characteristics in cancer patients’ illness narratives on Chinese TikTok - Julihati, Kaisa; Liu, Zheng (Frontiers in Communication, 2025)
Short-video platforms like Douyin (Chinese TikTok) have not only become a primary channel for people to access health information but have also evolved into an important medium for cancer patients to express their illness experiences. This study employs illness narrative theory and narrative identity theory to conduct both quantitative and qualitative analyses of 553 cancer narrative videos on the Douyin platform, aiming to explore the typological characteristics, identity construction strategies, and communication effects of cancer patients’ illness narratives. The findings reveal important patterns regarding cancer illness narrative characteristics and user engagement on Douyin. While narrative types characterized by actively fighting cancer dominate in video quantity, narratives focusing on daily life demonstrate superior user engagement. Two identity construction strategies prove effective: patient identities based on medical evidence and family member identities grounded in kinship relations. The analysis also shows that women and urban residents constitute the primary creators of cancer narratives on the platform. Additionally, we found that cancer narratives on the platform exhibit significant commercial characteristics, with some patients using narratives to gain economic support. These findings reveal the unique cultural characteristics of cancer illness narratives on short-video platforms, providing an empirical foundation for understanding health communication in digital environments, while offering insights for patients, medical institutions, and platforms to optimize health communication strategies.